Design and Build of Road Damage Information System in Madiun Regency Using Web Development Life Cycle Methods - Dwi Nor Amadi; Pradityo Utomo; Arief Budiman (Universitas Bina Darma, 2022)
Government infrastructure development is growing rapidly, starting from the central and provincial levels. One of the infrastructures currently being pushed by the government is road infrastructure. Both toll roads, regional roads, and district/city roads. Road infrastructure that has been built requires maintenance and repair. Road damage maintenance and repair in urban districts, especially Madiun Regency, Existing Road damage data is still recorded manually using paper, where the government needs help knowing data on road damage that has been recorded, which road conditions have not been repaired, and which have been fixed immediately. Because manual data is prone to wear and loss, tucked in with other manual files. So, the road improvement priority in Madiun Regency still needs to be put on target. For this reason, an information system is required to record the damage to road infrastructure in Madiun Regency. This information system was built using the web development life cycle (WDLC) method. We chose this method because it can be used in all web application development processes and can be modified or added to prototyping and looping to maximize results. The information system for road damage in Madiun Regency was developed using the PHP & MySQL programming languages. The result of this study is a road damage information system that contains updated data on road damage conditions in the Madiun district. Apart from being paperless, digitized data has the advantage of minimal damage and expected data loss and can help decision-makers prioritize repairs by looking at the data in the road damage information system.